Empowering solar photovoltaic logistic operations through cloud-enabled blockchain technology: a sustainable approach - Pan, HongYu; Bayanati, Mahmonir; Vaseei, Masoud; Chobar, Adel Pourghader (Frontiers in Energy Research, 2023)
In a world where renewable energy solutions are in high demand, solar photovoltaic (PV) systems are at the forefront, emphasizing the need for efficient and eco-friendly logistics. This coincides with the rise of blockchain technology as a game-changer in PV system management. Additionally, cloud computing is playing a pivotal role in transforming the IT landscape, providing seamless access to shared computing resources via the Internet. This research introduces a novel framework that utilizes cloud computing to enhance blockchain-based PV logistics. It employs a sophisticated mathematical model to optimize logistics components such as transportation, storage, inventory management, and supply chain coordination, with the goal of minimizing costs and improving overall efficiency. At the heart of this transformative paradigm lies a visionary cloud-based system, endowing PV logistic planners with the power of real-time access to mission-critical data. This infusion of data-driven decision-making capabilities fosters a seamless symphony of communication and enriches collaboration among stakeholders, setting the stage for monumental shifts in efficiency and management, ushering in a new era of sustainability and scalability within the photovoltaic industry. This technological synergy is not just about immediate gains. It is a testament to our commitment to improved energy sustainability and a testament to our shared vision of a greener future. In lockstep with the global pursuit of renewable energy solutions, this research lights the way toward a brighter, more sustainable tomorrow.